A Retrospective Cohort Study to Compare the Efficacy of Continuous Positive Airway Pressure and Non-Synchronised Nasal Intermittent Positive Pressure Ventilation as Primary Post Extubation Respiratory Support in Preterm Neonates Admitted for Severe Respiratory Distress Syndrome in a Tertiary Care NICU (GAIMS Journal of Medical Sciences, 2026)
Background - Evidence clearly shows that reducing the duration of invasive mechanical ventilation and early extubation helps to improve the long-term outcomes of preterm neonates. However, what is not clear is the initial mode of non-invasive support post extubation that may be provided to these preterm neonates. Resource limited public sector NICUs in developing countries like India often face a challenge of ensuring adequate number of machines to deliver NIPPV for all these preterm babies in post extubation period. Methods – This is a retrospective cohort study which included 60 neonates who were directly extubated to CPAP and were compared with 60 neonates extubated to non synchronised NIPPV, who were selected after propensity score matching with CPAP group. The primary outcome of interest was rate of extubation failure within 72 hours and need for escalation of respiratory support. Other outcomes that were looked at included the duration respiratory support; duration of hospital stay and rates of other complications between the two groups. Results – 13 babies in CPAP group experienced extubation failure while 11 in NIPPV group experienced it (p value = 0.84, cOR = 1.07); with results being not statistically significant. There was a significant reduction in duration of hospital stay (median = 5 days, p= 0.035, r= 0.11), however this did not translate to overall significant reduction in duration of hospital stay (p=0.48, r = 0.06) and other adverse outcomes. Kaplan Meier analysis revealed that probability of baby remaining extubated was also comparable in both groups. Conclusion- Standalone Bubble CPAP is equally efficacious as non synchronised NIPPV delivered by ventilator device in terms of preventing extubation failure and does not increase the overall duration of hospital stay and other adverse outcomes in preterm neonates. However more adequately powered randomised trials are needed to confirm these results.